2017
DOI: 10.1016/j.tranon.2016.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Features of Brain Metastases in Small Cell Lung Cancer: an Implication for Hippocampal Sparing Whole Brain Radiation Therapy

Abstract: PURPOSE: To assess the clinical features and distribution of brain metastases (BMs) of small cell lung cancer (SCLC) in the hippocampal and perihippocampal region, with the purpose of exploring the viability of hippocampal-sparing whole-brain radiation therapy (HS-WBRT) on reducing neurocognitive deficits. METHODS: This was a retrospective analysis of the clinical characteristics and patterns of BMs in patients with SCLC. Associations between the clinical characteristics and hippocampal metastases (HMs)/perihi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In Gondi's study, patients with primary small cell lung cancer and melanoma had higher incidence of melanoma patients. Similar to our results were reported by Guo's and coll 14 . Wan's study 17 found that the rate of metastases was 3.4 and 4.3% in hippocampus and subventricular zone.Wu's study 18 With available risk factors, we found that the risk of HI increases significantly and continuously with number of BMs.…”
Section: Discussionsupporting
confidence: 93%
“…In Gondi's study, patients with primary small cell lung cancer and melanoma had higher incidence of melanoma patients. Similar to our results were reported by Guo's and coll 14 . Wan's study 17 found that the rate of metastases was 3.4 and 4.3% in hippocampus and subventricular zone.Wu's study 18 With available risk factors, we found that the risk of HI increases significantly and continuously with number of BMs.…”
Section: Discussionsupporting
confidence: 93%
“…A known risk factor for HA region metastasis is a large number of BMs. 14 , 18 The current case was therefore unusual as this patient had a single BM in the HA region. Although this solitary BM was removed by surgical resection, stereotactic radiosurgery may be a good alternative.…”
Section: Discussionmentioning
confidence: 78%
“…Two retrospective studies examined the incidence of hippocampal metastasis exclusively in SCLC patients. 14 , 15 Guo et al 14 assessed a total of 1,594 BMs (at presentation or follow-up) in 180 SCLC patients. HA region metastasis was detected in 22 (12.2%) patients: 13 perihippocampal (≤ 5 mm of hippocampus) and nine hippocampal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of this study suggests the benefit of hippocampal sparing in limiting the neuropsychological sequelae of brain radiation, but with a risk of failures in the spared region. Two studies analysed the incidence of hippocampal metastasis (38,39). Guo et al (38), based on retrospective analysis of the clinical characteristics and patterns of brain metastases detected at the time of diagnosis or during the followup in patients with SCLC, concluded that the incidence of perihippocampal metastases (12%) may be acceptably low enough to justify hippocampal-sparing techniques for SCLC.…”
Section: Toxicity Of Pcimentioning
confidence: 99%